Comparative efficacy, tolerability, and survival outcomes of various radiopharmaceuticals in castration-resistant prostate cancer with bone metastasis: a meta-analysis of randomized controlled trials - Tunio M; Al Asiri M; Al Hadab A; Bayoumi Y (Dove Medical Press, 2015)
Mutahir Tunio,1 Mushabbab Al Asiri,1 Abdulrehman Al Hadab,1 Yasser Bayoumi2 1Radiation Oncology, Comprehensive Cancer Center, King Fahad Medical City, Riyadh, Saudi Arabia; 2Radiation Oncology, National Cancer Institute, Cairo University, Cairo, Egypt Background: A meta-analysis was conducted to assess the impact of radiopharmaceuticals (RPs) in castration-resistant prostate cancer (CRPC) on pain control, symptomatic skeletal events (SSEs), toxicity profile, quality of life (QoL), and overall survival (OS).Materials and methods: The PubMed/MEDLINE, CANCERLIT, EMBASE, Cochrane Library database, and other search engines were searched to identify randomized controlled trials (RCTs) comparing RPs with control (placebo or radiation therapy) in metastatic CRPC. Data were extracted and assessed for the risk of bias (Cochrane’s risk of bias tool). Pooled data were expressed as odds ratio (OR), with 95% confidence intervals (CIs; Mantel–Haenszel fixed-effects model).Results: Eight RCTs with a total patient population of 1,877 patients were identified. The use of RP was associated with significant reduction in pain intensity and SSE (OR: 0.63, 95% CI: 0.51–0.78, I2=27%, P<0.0001), improved QoL (OR: 0.71, 95% CI: 0.55–0.91, I2=65%, three trials, 1,178 patients, P=0.006), and a minimal improved OS (OR: 0.84, 95% CI: 0.64–1.04, I2=47%, seven trials, 1,845 patients, P=0.11). A subgroup analysis suggested an improved OS with radium-223 (OR: 0.68, 95% CI: 0.51–0.90, one trial, 921 patients) and strontium-89 (OR: 0.21, 95% CI: 0.05–0.91, one trial, 49 patients). Strontium-89 (five trials) was associated with increased rates of grade 3 and 4 thrombocytopenia (OR: 4.26, 95% CI: 2.22–8.18, P=0.01), leucopenia (OR: 7.98, 95% CI: 1.82–34.95, P=0.02), pain flare (OR: 6.82, 95% CI: 3.42–13.55, P=0.04), and emesis (OR: 3.61, 95% CI: 1.76–7.40, P=0.02).Conclusion: The use of RPs was associated with significant reduction in SSEs and improved QoL, while the radium-223-related OS benefit warrants further large, RCTs in docetaxel naive metastatic CRPC patients. Keywords: radiopharmaceuticals, castration-resistant prostate cancer, meta-analysis, pain control, symptomatic skeletal events, quality of life, overall survival